Efektywnosc instytucji a jakosc zycia w kontekscie globalnej gospodarki wiedzy - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
– The purpose of the article was to evaluate the relationship between the level of institutional effectiveness in the context of global knowledge economy (KBE) and quality of life for the EU countries in the years 2004 and 2010. To measure the intitutional effectiveness authors proposed a synthetic indicator, which was constructed with the TOPSIS method. Variables cocnerning four aspects characterizing the institutional system in the context of the country's ability to exploit the potential of KBE were used in the research. The data was obtained from the Fraser Institute database. The Human Development Index was used as a measure of quality of life. In order to evaluate the relation between institutional effectiveness for KBE and quality of life correlation analysis was used. It allowed to identify positive relationship between the institutional factors associated with the use of the potential of KBE on the quality of life.
Keywords: 330; efficiency of the institutional system; quality of life; Human Deve-opment Index; global knowledge-based economy